Bust of Shri Jagannath Shankarseth at Banganga cremation ground - Ghosh, Ayan (2023)
Among the many contributions of philanthropist Jagannath Shankarseth was the donation of land to the north of Banganga Tank to be used as burning ground for those Hindus who wished to be cremated at Walkeshwar in the vicinity of the Banganga Tank. A bust of Jagannath Shankarseth is now installed at the crematorium which is also named after him.